Policies and working conditions of the educational sector in Costa Rica - Morales Zúñiga, Luis Carlos (2011)
This essay approaches from a sociological perspective and especially from some analytical elements of sociology of education and sociology of work, certain aspects of the national education current policy, specifically, those related to working conditions of teachers. This paper raises the relationship between working conditions for teachers and State policy in relation to national educational problems, policies that are unuseful to achieve a reform of the education system, as a result of the impossibility of think about social change, and legitimating of educational policies in the current education system. The emphasis of the analysis of working conditions is the subject of salaries, the job instability, and the workload for teachers.